Let it be done: Antecedents of tax compliance and its implications on the self-esteem of Filipino self-assessed taxpayers - Dy Buco, Darla C. (Animo Repository, 2024)
This study explores the relationship between financial strain, negative tax affect, and diskarte modeling with tax compliance among self-assessed taxpayers in the Philippines, guided by the General Strain Theory (GST), and the association of tax compliance on state self-esteem. Online surveys were conducted among Filipino self-assessed taxpayers, and the collected data was analyzed using correlation tests. The findings show that financial strain, negative affect, and diskarte modeling have a slight negative correlation with taxpayers' compliance alongside positive correlations with avoidance and evasion. Furthermore, a positive link was found between tax compliance and state self-esteem. This research contributes to tax literature by empirically examining relationships in a developing country context and exploring the impact of cultural factors on tax behavior, shedding light on patterns distinct to the Philippines. The study extends the General Strain Theory and Social Learning Theory’s applicability to individual financial behaviors.